(untitled) (Bangladesh Journal of Medical Science, 2021)
Introduction:Early shared reading experiences positively predict outcomes in language andliteracy development of children who experience rich communicative and affective interactionsby parents during story narration. However, research is yet to be systematically exploremother’s practices and perceptions towards story narration and how employment of mothermay influence their perspectives and practices Aim:Toanalyse the perspectives of employedand unemployed mothers of typically developing children between 2 to 5 years towards story narration. Materials and Methods: The study followed a cross sectional design. A total of 60participants were selected in three age groups (Group I, II & III) of employed and unemployedmothers. A questionnaire was developed to analyse perceptions and practices of mother oftypically developing children between 2 to 5 years towards story narration. The responses werescored and analysed using SPSS Software, where a Chi-Square Test was performed to checkthe association. Results:Chi-square analysis revealed no significant association of employmentin maternal perceptions towards story narration activities. Conclusion:The study revealed thatemployment does not influence maternal perceptions towards story narration. The increase inmean score with age indicated a positive change in mother’s perception. This finding is animportant contributing factor to understand the role of mothers in children’s developing languageand early literacy skills. The study emphasises and highlights the lacuna in early interaction ofmothers in pre-literacy based activities, which can contribute to better academic performancein later stages. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.86-94